2021
DOI: 10.1080/1331677x.2021.1926305
|View full text |Cite
|
Sign up to set email alerts
|

A circular economy model for fossil fuel sustainable decisions based on MADM techniques

Abstract: Fossil fuels as the primary energy source create career opportunities, provide industries with vital raw material and energy resources, have harmful emissions to the environment and are also related to finite natural resources. They rely on them as the main source of energy supply is unsustainable. Sustainability assessment tools may be useful in developing a more sustainable scenario. However, the resiliency of nature is not taken into account in this linear assessment. The detrimental effect of these fuels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…The EXTENDED-SWARA method is used for evaluating the CE criteria. Then they used the MARCOS method for ranking, and they showed that gas is the most sustainable fuel of the two others [21]. Hashemkhani Zolfani, et al developed a novel integrated decision-making tool for selecting the most profitable market.…”
Section: A Summary Of Sfa Backgroundmentioning
confidence: 99%
“…The EXTENDED-SWARA method is used for evaluating the CE criteria. Then they used the MARCOS method for ranking, and they showed that gas is the most sustainable fuel of the two others [21]. Hashemkhani Zolfani, et al developed a novel integrated decision-making tool for selecting the most profitable market.…”
Section: A Summary Of Sfa Backgroundmentioning
confidence: 99%
“…In the article, this approach has been extended via a focus on sustainable development: sustainability (economic and environmental)—income–savings–propensity to invest–investment–productive and non-productive assets (accumulation). The analysed problems also correspond to the broader concept of a circular economy, which emphasises the optimisation of resource management [ 1 ], and thus involves the economics of sustainable development [ 2 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…But, when these GHGs absorb the IR radiation, it becomes trapped in our atmosphere and redirects back to the Earth's surface, causing a net heating effect. Our current society and economy relies on burning fossil fuels, burning these fuels creates CO 2 and is thus a cause of climate change [11,20].…”
Section: Introductionmentioning
confidence: 99%